DEVELOPMENT TENDENCIES OF THE MODERN ELECTRICAL INDUSTRY ON A GLOBAL SCALE (Marketing Journal, 2025)
This article analyzes the modern global development trends in the electrical engineering industry. Specifically, it explores areas such as digital transformation, artificial intelligence, green energy systems, energy storage technologies, Industry 4.0, 5G, and future communication technologies. Based on advanced international experience, the study evaluates the technological transformations, their economic and environmental impacts, and the global competitiveness of the electrical engineering sector. Furthe rmore, using forecasting methods, the article outlines prospective 462 development directions and proposes scientifically grounded recommendations for modernizing Uzbekistanʼs electrical engineering industry.
Keywords: electrical engineering industry; global trends; digital transformation; artificial intelligence; green energy; international experience; smart grids; 5G technology; energy storage; Industry 4.0